Comparing trimodal therapy with radical cystectomy in muscle-invasive bladder cancer: an updated meta-analysis - Al-Qudimat, Ahmad R.; Singh, Kalpana; Ojha, Laxmi K.; Moustafa, Diala Alhaj; Elaarag, Mai; Al-Zoubi, Raed M.; Aboumarzouk, Omar M. (Frontiers in Surgery, 2023)
We conducted this meta-analysis to compare the two-muscle invasive bladder cancer (MIBC) treatment modalities in terms of cancer-specific survival (CSS) and other outcome indicators.A systematic review and meta-analysis were performed and followed the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. We The search was achieved using Scopus, PubMed, Cochrane database, EMBASE, Chinese biomedicine literature database, Wan fang databases China National Knowledge Internet databases between 1966 to Dec 2023. This review protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) No. (CRD42023398977).Result: Fourteen studies total of 54,816 bladder cancer patients with 6,228 from the trimodal therapy (TMT) group and 48,588 from the radical cystectomy (RC) group were included in this study. In accordance with the results, the RC group had a higher rate of survival than the TMT group [pooled hazard ratio (HR) = 1.23, 95% CI: 1.18-1.28, Z = 1.46, P 0.001], According to the data, RC group was having better survival as compared to TMT group [pooled hazard ratio (HR) = 1.23, 95% CI: 1.18-1.28, Z = 1.46, P = 0.14], In terms of CSS, patients in the RC group had longer CSS compared to the TMT group (pooled HR = 1.47, 95% CI: 1.29-1.67, Z = 5.893, P < 0.001). Compared with RC, TMT is associated with a significant increase in both types of mortality, the pooled HR:1.30, P < 0.001.Overall, this meta-analysis suggests that treatment with RC may be associated with better overall survival. Moreover, patients in the RC group demonstrated longer cancer-specific survival (CSS) compared to those receiving TMT. Additionally, patients who received TMT had a higher risk of all-cause mortality in comparison to those who underwent RC.